2017
DOI: 10.1111/nana.12332
|View full text |Cite
|
Sign up to set email alerts
|

Performing the national territory: The geography of national‐day celebrations

Abstract: The nation is a relatively abstract imagined community that is visualised through a variety of symbols as well as communicative and performative practices. In this paper, we explore how the national territory, one of the foundations of the nation‐state, is performed on national‐day celebrations and brings the nation into being. Drawing on ethnographic research on national days in Burkina Faso, Côte d'Ivoire and Ghana, we show how the state's internal administrative divisions and ethnic differences are at once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…While large-scale, state-led centralized nation-building programs do not fit well the African experience, 3 many studies highlight ways in which African governments used nationalist iconography, relying especially on visual and performing arts, such as dance (Schauert, 2014;Schramm, 2000), music (Askew, 2002;Turino, 2000), festivals (Apter, 1996;Lentz, 2001;N'Guessan et al, 2017), architecture (Hess, 2000), or currency and postage imagery (Fuller, 2008). After noting over the years the lack of cultural content of African nationalism (1985,1986), Crawford Young in his recent writing (2012) concluded that national identity is buttressed by "a limited repertoire of common icons" (2012, p. 309), or "banal" symbols, to borrow Michael Billig's (1995) term.…”
Section: Pathways To Nation-buildingmentioning
confidence: 99%
“…While large-scale, state-led centralized nation-building programs do not fit well the African experience, 3 many studies highlight ways in which African governments used nationalist iconography, relying especially on visual and performing arts, such as dance (Schauert, 2014;Schramm, 2000), music (Askew, 2002;Turino, 2000), festivals (Apter, 1996;Lentz, 2001;N'Guessan et al, 2017), architecture (Hess, 2000), or currency and postage imagery (Fuller, 2008). After noting over the years the lack of cultural content of African nationalism (1985,1986), Crawford Young in his recent writing (2012) concluded that national identity is buttressed by "a limited repertoire of common icons" (2012, p. 309), or "banal" symbols, to borrow Michael Billig's (1995) term.…”
Section: Pathways To Nation-buildingmentioning
confidence: 99%
“… 9 There are further important aspects of the parades that cannot be discussed with sufficient detail in this paper, such as the organisation of space, both on a macro and a micro level (on this aspect, see Gabriel et al., 2016; and N’Guessan et al., 2017). Furthermore, it is worthwhile analysing the music that is played during the parade (see Hoffmann, 2003; Schramm, 2008), and the way the media covers the parade (see e.g.…”
mentioning
confidence: 99%
“… 11 There are simultaneous celebrations in the country’s regions (N’Guessan et al., 2017); in this paper, however, we focus on the parade of the central celebration marked by the presence of the head of state.…”
mentioning
confidence: 99%